Searching for the true origin of the red fluorescence of leaf-derived carbon dots. Issue 4 (16th January 2023) - Qin, Fu; Bai, Jianliang; Zhu, Yaqing; He, Pinyi; Wang, Xinyu; Wu, Shuang; Yu, Xu; Ren, Lili
Abstract : The origin of the red fluorescence for leaf-derived CDs was firstly found to be from the molecular fluorophore chlorophyll, not the core state or surface functional groups of the CDs. Abstract : We report for the first time that the red fluorescence of leaf-derived carbon dots is derived from chlorophyll, and a possible formation structure is proposed. By controlling the solvothermal reaction temperature, the new luminescence center of CDs can be adjusted. This work provides unprecedented insights into the luminescence mechanism of biomass-derived CDs.